EFEKTIVITAS PENERAPAN METODE UMMI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QUR’AN DI SD ISLAM AQZIA TELUK KUANTAN - Olga Novita; Zulhaini Zulhaini; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
This research is motivated by a problem found in the initial observations of the author at School Of Islam Aqzia Teluk Kuantan, symptoms are found as follow: 1. Teachers have already applied the Ummi Method well but still some student’ achievement were not satisfied. 2. There are still some students prefer playing with their friends beside to paying attention to teachers in learning Al-Qur’an process by using Ummi Method so, their ability foe each chapter would different. 3. There are still students who read Al-Qur’an slowly. This research aims to know the Effectiveness Of Using Ummi Method Toward Students’ Leraning Result In Elementary School Of Islam Aqzia Teluk Kuantan. Data collection is done through observation, interview, forms fulfilling, and documentation. And writer also used causal-associative and simple regression linear to analize data. Me took 42 samples to support this research, we explained the effectiveness of Ummi Method. Based on the questionaires given, it shows that there is no effectivity of using Ummi Method in teaching learning process. It didn’t give a significant differences in learning achievement. The index t is 0,402 < t table 1,690 Ha is refused and Ho is accepted. Determinant point is =0.004 or 00.4%. in conclusion, there is no effectindy between Ummi Method and Students’ Learning Achievement of Students In Elementary School Teluk Kuantan. Key Words : Ummi Method, Students’s Learning Achievement